Advancements in Managing Intractable Raynaud Phenomenon: The Role of Integrated Neurectomy and Sympathectomy - Lien, Po-Hao; Chen, Shih-Heng (Seminars in Plastic Surgery, 2025)
Raynaud's phenomenon (RP) is characterized by digit discoloration including pallor, cyanosis, and rubor. While some experience only mild numbness or tingling during RP attacks, many progress to severe conditions, including intractable pain, nonhealing digital ulcers, and even self-amputation. Although mild symptoms can often be managed conservatively through lifestyle modifications, such as avoiding triggering factors, or with pharmacological interventions, surgical treatments are often required for those with persistent pain and ulcers. Advances in microsurgical techniques have introduced peripheral sympathectomy, peripheral neurectomy, and distal artery bypass as promising options for managing refractory and severe cases of RP. This review explores the epidemiology, pathophysiology, and particularly the evolution of microsurgical interventions for the treatment of RP.
Keywords: Raynaud's phenomenon; connective tissue disease; microsurgical intervention; sympathectomy; arterial bypass